Ідентифікація переважної мови спілкування людини - Лазоренко, Я.С.; Сініцин, І.П.; Шевченко, В.Л. (Проблеми програмування, 2022)
Зі збільшенням обсягів переміщення населення, як тимчасового, так і на тривалий час через військові дії, роботу тощо, виникає потреба в удосконаленні процесів контролю переміщення та ідентифікації груп людей. Першочерговою потребою є виявлення приналежності людини до певної національності чи території переважного перебування. Крім того, це може бути корисно й для наукових соціо-політичних досліджень, а також сфери туризму, адже така ідентифікація людей за мовним середовищем може говорити й про культурне середовище, що дозволить краще передбачати вподобання цілих груп клієнтів. Обробку аудіозапису мовлення диктора було розбито на 3 етапи, кожен із яких містить визначену покрокову інструкцію процесу підготовки та обробки даних. Спочатку було проведено аналіз самого звуку, адже голос і вимова є одними із найшвидших і при цьому найефективніших інструментів ідентифікації особи чи групи осіб. Потім аудіозапис було конвертовано в текст і проведено аналіз лексичного складу досліджуваного фрагменту розмови. У кінці результати роботи програми, отримані в попередніх двох етапах, були комплексно оцінені за визначеними в ході теоретичного дослідження критеріями з присвоєнням їм вагових коефіцієнтів. Як підсумок, було отримано припущення про мовне середовище диктора. У роботі були розглянуті чинники, що впливають на формування вимови та побудови різних інтонацій, особливості взаємозв’язку тексту та звуку, а також були математично формалізовані деякі залежності між звуковими параметрами та вимовою звуків у російській і українській мовах. Тема роботи широкою, оскільки розглядає не тільки лексичні, а й акустичні особливості мовлення. Тож враховуються не лише мінливі чи ситуативні якості, наприклад, словниковий запас розмови, а й властиві людині незалежно від контексту розмови, її емоційного стану чи того, якою мовою вона говорить у даний момент. Розглянуті у роботі критерії дозволяють робити припущення про «природну», звичну диктору мову, тобто ту, якою він спілкується давно й більшість часу. With the great increase of population movement, caused either by temporarily needs due to travelling or by long-term ones due to work, etc. , there appears a need to improve the processes of movement control and identification of groups of people. The primary need is to identify if a person belongs to a certain nationality or territory of primary residence. In addition, it can be useful for scientific social and political researches, as well as for the field of tourism and entertainment. Such identification of people by language environment can also help to find out more about the cultural environment, which will make possible to predict the preferences of entire groups of customers better. The analysis of the audio recording of the speaker’s speech was divided into 3 stages, each of which contains a defined step-by-step instruction for the processes of data preparation and handling. Firstly, the sound itself was analyzed, because voice and pronunciation are one of the fastest and most effective tools for identifying a person or a group of people. Then the audio recording was converted into text and an analysis of the lexical composition of the studied fragment of the conversation was done. At the end, the results of the program, got in the previous two stages, were compared and the complex evaluations were done according to the criterias determined in the theoretical researches. The mentioned criterias were used with weighting factors assigned to them. As a result, an assumption about the speech environment of the speaker was given by the program. The work also describes the factors which affects the formation of pronunciation and the change of various intonations, the relationship between text and sound. Some dependencies between sound parameters and the pronunciation of sounds in the Russian and Ukrainian languages were mathematically formalized. The topic of the work is wide, as it considers not only lexical, but also acoustic features of speech. In this way, not only changeable or situational qualities are taken into account, for example, the vocabulary of the conversation, but also those ones that are related to the person regardless of the context of the conversation, his or her emotional state or what language he or she is speaking at the very moment. The criterias considered in the work can help to make assumptions about the speaker’s «natural», most familiar language, in other words the language he or she uses most of the time in life.